2016
DOI: 10.1177/2047487315625235
|View full text |Cite
|
Sign up to set email alerts
|

Could the two-minute step test be an alternative to the six-minute walk test for patients with systolic heart failure?

Abstract: The two-minute step test is well tolerated by patients with heart failure and may thus be considered as an alternative for the six-minute walk test.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
41
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(45 citation statements)
references
References 28 publications
2
41
1
1
Order By: Relevance
“…On the other hand, two step test can be used to assess Cardiovascular diseases physical tolerance (Wegrzynowska-Teodorczyk et al, 2016) and at the same time is linked to higher risk of fall as was found in this study. However, we did not nd other functional tests to be linked to fall risk among this group may be related to the fact that most of participants were less than 70 y and many of them still working.…”
Section: Discussionmentioning
confidence: 58%
“…On the other hand, two step test can be used to assess Cardiovascular diseases physical tolerance (Wegrzynowska-Teodorczyk et al, 2016) and at the same time is linked to higher risk of fall as was found in this study. However, we did not nd other functional tests to be linked to fall risk among this group may be related to the fact that most of participants were less than 70 y and many of them still working.…”
Section: Discussionmentioning
confidence: 58%
“…Studies have shown the efficacy of the stationary gait test for other populations such as the healthy elderly and subjects with arterial hypertension, heart failure, and cervical compressive myeloma. 30,22,31,32 The STVR-6 is a functional capacity assessment test that only requires a small space. Moreover, it is practical and simple to use.…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, it can be performed in the hospital environment for acute conditions with better monitoring. 31 It is considered safe because it avoids falls, and it can be performed using walking aids. It can also be used by individuals with altered balance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Physical fitness was evaluated using selected physical tasks from the Functional Fitness Test (FFT) for Older Adults . For the purpose of this study, we used the following elements of FFT (the remaining two components of FFT assess the patient's lower and upper body flexibility and were not analysed): ‘Up and go’ (assessment of agility and dynamic balance)—patient is asked to stand up from a chair as fast as possible, walk around a pole placed within 2.44 m, and return to the baseline position.…”
Section: Methodsmentioning
confidence: 99%